Dual-Targeting Small-Molecule Inhibitors of the Staphylococcus aureus FMN Riboswitch Disrupt Riboflavin Homeostasis in an Infectious Setting. Issue 5 (18th May 2017) - Wang, Hao; Mann, Paul A.; Xiao, Li; Gill, Charles; Galgoci, Andrew M.; Howe, John A.; Villafania, Artjohn; Barbieri, Christopher M.; Malinverni, Juliana C.; Sher, Xinwei; Mayhood, Todd; McCurry, Megan D.; et al.
Summary: Riboswitches are bacterial-specific, broadly conserved, non-coding RNA structural elements that control gene expression of numerous metabolic pathways and transport functions essential for cell growth. As such, riboswitch inhibitors represent a new class of potential antibacterial agents. Recently, we identified ribocil-C, a highly selective inhibitor of the flavin mononucleotide (FMN) riboswitch that controls expression of de novo riboflavin (RF, vitamin B2) biosynthesis in Escherichia coli . Here, we provide a mechanistic characterization of the antibacterial effects of ribocil-C as well as of roseoflavin (RoF), an antimetabolite analog of RF, among medically significant Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA) and Enterococcus faecalis . We provide genetic, biophysical, computational, biochemical, and pharmacological evidence that ribocil-C and RoF specifically inhibit dual FMN riboswitches, separately controlling RF biosynthesis and uptake processes essential for MRSA growth and pathogenesis. Such a dual-targeting mechanism is specifically required to develop broad-spectrum Gram-positive antibacterial agents targeting RF metabolism. Graphical Abstract: Highlights: Ribocil-C and roseoflavin selectively target bacterial non-coding RNA elements Each agent inhibits two distinct FMN riboswitches controlling riboflavin metabolism Their mechanism is conserved in Staphylococcus aureus and Enterococcus faecalis Dual targeting of FMN riboswitches offer novel antibiotic discovery opportunities Abstract : Wang et al. demonstrate that ribocil-C and roseoflavin selectively target functionally related non-coding RNA structural elements termed FMN riboswitches controlling gene expression of riboflavin biosynthesis and uptake. Such targets and cognate inhibitors offer new opportunities and challenges to antibiotic discovery.